Association between vigorous physical activity and life satisfaction in adolescents - Feng, Bin; Xu, Ke; Zhou, Panpan (Frontiers in Public Health, 2022)
Purpose: This study surveys vigorous physical activity (VPA) and life satisfaction’s correlation according to the differences of adolescents’ gender and age. Methods: According to the Health Behaviour in School-aged Children (HSBC) investigation which the research applies, the research siphons sample of 11- to 15-year-old adolescents representatively to perform a cross-sectional analysis. Participants provided information about their background, lifestyle habits, frequency, as well as length of VPA per week. Besides, these adolescents provided the rating of their life satisfaction. Logistic models were carried out to analyse the association between VPA frequency or duration every week and life satisfaction among adolescents. Results: Among the 214,080 (49.2% male) adolescents studied, both male and female participants exercising more than once per week who reported high life satisfaction had the highest percentage. In the results representing the whole sample, adolescents exercising more hours every week were less likely to obtain high life satisfaction. Moreover, adolescents aged 11 or 13 years old tended to report higher life satisfaction when they conducted VPA more frequently every week. On the contrary, adolescents aged 15 were observed to report higher life satisfaction when they carried out VPA less frequently but for longer periods per week. Conclusions: In conclusion, this research provided a cross-section research on the VPA and life satisfaction’s correlation among adolescents aged 11-15. Considering life satisfaction is regarded as an indicator of adolescents' psychological health development, our study supports and extends the evidence for the importance of VPA in adolescence.